Producing the “Others”: The Development of Kraevedenie in Chukotka - Gavrilova, Sofia (Études Inuit Studies, 2021)
Among various methods of mastering and governing the Far East and the Arctic, Soviet authorities implemented a specific system of knowledge production (kraevedenie) and its institutional centers: kraevedcheskii museums. The research activities and exhibition policies of museums across the former Soviet Union were guided by a group of Moscow-based policymakers and scientists who developed a strict exhibition structure and associated narratives. This article relates the history of several kraevedcheskii museums in Chukotka against a backdrop of center-periphery and colonial relationships in the former Soviet Union, and also analyzes the contemporary exhibitions of these museums and their role within Indigenous communities.